MicroRNA-300 Regulates the Ubiquitination of PTEN through the CRL4BDCAF13 E3 Ligase in Osteosarcoma Cells - Zhi Chen; Wei Zhang; Kaibiao Jiang; Bin Chen; Kun Wang; Lifeng Lao; Canglong Hou; Fei Wang; Caiguo Zhang; Hongxing Shen (Elsevier, 2018)
Cullins, critical members of the cullin-RING ubiquitin ligases (CRLs), are often aberrantly expressed in different cancers. However, the underlying mechanisms regarding aberrant expression of these cullins and the specific substrates of CRLs in different cancers are mostly unknown. Here, we demonstrate that overexpressed CUL4B in human osteosarcoma cells forms an E3 complex with DNA damage binding protein 1 (DDB1) and DDB1- and CUL4-associated factor 13 (DCAF13). In vitro and in vivo analyses indicated that the CRL4BDCAF13 E3 ligase specifically recognized the tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10) for degradation, and disruption of this E3 ligase resulted in PTEN accumulation. Further analyses indicated that miR-300 directly targeted the 3' UTR of CUL4B, and DNA hypermethylation of a CpG island in the miR-300 promoter region contributed to the downregulation of miR-300. Interestingly, ectopic expression of miR-300 or treatment with 5-AZA-2'-deoxycytidine, a DNA methylation inhibitor, decreased the stability of CRL4BDCAF13 E3 ligase and reduced PTEN ubiquitination. By applying in vitro screening to identify small molecules that specifically inhibit CUL4B-DDB1 interaction, we found that TSC01131 could greatly inhibit osteosarcoma cell growth and could disrupt the stability of the CRL4BDCAF13 E3 ligase. Collectively, our findings shed new light on the molecular mechanism of CUL4B function and might also provide a new avenue for osteosarcoma therapy.